Structure Analysis of Effective Chemical Compounds against Dengue Viruses Isolated from Isatis tinctoria - Bo Gao; Jianming Zhang; Lianhui Xie (Canadian Journal of Infectious Diseases and Medical Microbiology)
The history of Chinese herb research can be traced back to thousands of years ago, and the abundant knowledge accumulated for these herbs makes them good candidates for developing new natural drugs. Isatis tinctoria is probably the most well-studied Chinese herb, which has been identified to be effective against dengue fever. However, the underlying biological mechanisms are still unclear. In this study, we adopt combined methods of bioactive trace technology and phytochemical extraction and separation, to guide the isolation and purification of the effective chemical constituents on the water-soluble components of aerial parts of Isatis tinctoria. In addition, we apply polarimetry and 1D or 2D nuclear magnetic resonance (NMR) spectroscopy to identify their structures, which lay a foundation for further study on the biological mechanisms underlying medicinal effects of Isatis tinctoria using in vitro and in vivo experiments. Specifically, we identify and infer the structures of 27 types of chemical compounds named GB-1, GB-2, …, GB-27, respectively, among which GB-7 is a novel compound. Further study of these compounds is critical to reveal the secrets behind the medicinal effects of Isatis tinctoria.